Promosi Kesehatan Melalui Media Sosial, Literasi Kesehatan, dan Kebijakan Physical Distancing Terhadap Perilaku Pencegahan COVID-19 : Health Promotion Through Social Media, Health Literacy, and Physical Distancing Policies on COVID-19 Prevention Behavior - Riva Yunita; Achmad Lukman Hakim; Agustina Sari (MPI Press, 2021)
Introduction: Coronavirus Disease 2019 (COVID-19) is a contagious disease caused by a coronavirus where the virus attacks the respiratory tract and can infect humans and animals. Therefore, preventive measures to break the chain of transmission of infectious diseases must be carried out as quickly as possible in breaking the chain of transmission of COVID-19 Objectives: The purpose of the study was to determine the relationship between health promotion through social media, health literacy, and physical distancing policies on COVID-19 behavior prevention behavior in urban communities in 2020. Methods: The research method is quantitative with a cross sectional research design. The population in this research is all urban people who live in the DKI Jakarta area. The sampling technique used accidental sampling of 100 respondents. The data used are primary data through distributing questionnaires and secondary data derived from Jakarta's COVID-19 monitoring data Results: Data analysis was performed univariate and bivariate with the Pearson product moment correlation test. The results showed the relationship between health promotion through social media (with p-value = 0.001 and r = 0.315), health literacy (with p-value = 0.000 and r = 0.613), and physical distancing policy (with p-value = 0.000 and r = 0.973) on behavior Conclusion: prevention of COVID-19 in urban communities. It is hoped that the government will not hesitate in carrying out policies in reducing the spread of COVID-19 and promoting coordination with various related parties.